Personality, Psychopathology, and Psychotherapy: A Pre-specified Analysis Protocol for Confirmatory Research on Personality–Psychopathology Associations in Psychotherapy Outpatients - Hengartner, Michael P.; Yamanaka-Altenstein, Misa (Frontiers in Psychiatry, 2017)
The role of personality trait variation in psychopathology and its influence on the outcome of psychotherapy is a burgeoning field. However, thus far most findings were based on controlled clinical trials that may only poorly represent real-world clinical settings due to highly selective samples mostly restricted to patients with major depression undergoing anti-depressive medication. Focusing on personality and psychopathology in a representative naturalistic sample of psychotherapy patients is therefore worthwhile. Moreover, up to date hardly any confirmatory research has been conducted in this field. Strictly confirmatory research implies two major requirements: firstly, specific hypotheses, including expected effect sizes and statistical approaches to data analysis, must be detailed prior to inspection of the data, and secondly, corresponding protocols have to be published online and freely available. Here we introduce a longitudinal naturalistic study aimed at examining, firstly, the prospective impact of baseline personality traits on the outcome of psychotherapy over a 6-month observation period, secondly, the stability and change in personality traits over time, thirdly, the association between longitudinal change in psychopathology and personality, fourthly, the agreement between self-reports and informant-rating of personality, and fifthly, the predictive validity of personality self-reports compared to corresponding informant-ratings. For it we comprehensively state a-priori hypotheses, predict the expected effect sizes and detail the statistical analyses that we intend to conduct to test these predictions. Such a stringent confirmatory design increases the transparency and objectivity of psychopathological research, which is necessary to reduce the rate of false-positive findings and to increase the yield of scientific research.